Vaccine efficacy and iron deficiency: an intertwined pair?. Issue 9 (September 2021) - Drakesmith, Hal; Pasricha, Sant-Rayn; Cabantchik, Ioav; Hershko, Chaim; Weiss, Guenter; Girelli, Domenico; Stoffel, Nicole; Muckenthaler, Martina U; Nemeth, Elizabeta; Camaschella, Clara; Klenerman, Paul; Zimmermann, Michael B
Summary: Vaccines are the most effective measure to prevent deaths and illness from infectious diseases. Nevertheless, the efficacy of several paediatric vaccines is lower in low-income and middle-income countries (LMICs), where mortality from vaccine-preventable infections remains high. Vaccine efficacy can also be decreased in adults in the context of some common comorbidities. Identifying and correcting the specific causes of impaired vaccine efficacy is of substantial value to global health. Iron deficiency is the most common micronutrient deficiency worldwide, affecting more than 2 billion people, and its prevalence in LMICs could increase as food security is threatened by the COVID-19 pandemic. In this Viewpoint, we highlight evidence showing that iron deficiency limits adaptive immunity and responses to vaccines, representing an under-appreciated additional disadvantage to iron deficient populations. We propose a framework for urgent detailed studies of iron–vaccine interactions to investigate and clarify the issue. This framework includes retrospective analysis of newly available datasets derived from trials of COVID-19 and other vaccines, and prospective testing of whether nutritional iron interventions, commonly used worldwide to combat anaemia, improve vaccine performance.